Reconfiguração do star system através do influenciador digital: um estudo de caso da celebridade gkay - Silva, Mateus Silomar Melo da (2020)
The present qualification work focuses on the study of Communication, specifically on how media platforms can build and drive anonymous people to become celebrities from digital media and cyberculture, such as the so-called digital influencers. The study aims to demonstrate that the star system proposed by Edgar Morin has reconfigured itself through digital platforms and understand how users considered digital influencers have been solidifying in post-mass media. Considering that mobile devices have enabled a new phase of consumption and content production, we seek to understand this process of how ordinary individuals gain notoriety through the internet. For this research, we do a case analysis of digital influencer Gessica Kayane (Gkay) who was one of the first users to gain prominence in the media and the internet with instant video applications. For this, we analyzed the user page in the Instagram application to understand how this process of building content is made from the term star system proposed by Edgar Morin. We are using concepts: celebrity, star system, digital media as well as post-mass media.